2015
DOI: 10.1007/s10620-015-3773-y
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis Regression Explains Differences in Outcome in HIV-/HCV-Coinfected Patients with Cirrhosis After Sustained Virological Response

Abstract: Fibrosis regression after SVR is associated with the highest reduction in death of any cause, liver-related mortality, and liver-related complications in HIV-/HCV-coinfected patients with cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…Treatment regimens for HCV are rapidly changing, and there is a great need for further studies on the effect of each regimen on liver fibrosis. Fibrosis regression has been shown to decrease the risk of HCC and mortality [ 14 , 41 ], but many patients are offered HCV treatment after fibrosis has been established. Since our study found persistently elevated LS in many patients, early diagnosis and treatment before fibrosis has been established is necessary to maximize the benefits of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment regimens for HCV are rapidly changing, and there is a great need for further studies on the effect of each regimen on liver fibrosis. Fibrosis regression has been shown to decrease the risk of HCC and mortality [ 14 , 41 ], but many patients are offered HCV treatment after fibrosis has been established. Since our study found persistently elevated LS in many patients, early diagnosis and treatment before fibrosis has been established is necessary to maximize the benefits of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While cirrhosis-related complications did not occur among patients who regressed from METAVIR F4 to 6F2, the incidence of cirrhosis-related complications per 100 person-years was 4 among those who remained with F3 or F4 after therapy (p = 0.002). Although limited by the use of transient elastography for fibrosis regression assessment, the link between fibrosis regression and beneficial clinical outcome was recently confirmed among patients with a HCV-HIV coinfection [46]. Histological improvement may also explain the reduction in the hepatic venous pressure gradient (HVPG) which has been observed following HCV eradication with IFN-based therapy [47,48].…”
Section: Regression Of Hepatic Fibrosis and Cirrhosis Following Svrmentioning
confidence: 99%
“…Fibrosis regression has been shown to decrease the risk of cirrhosis and hepatocellular carcinoma and mortality. 27,28 This study shows improvement in major laboratory parameters viz; AST, ALT, INR, AFP, platelets, albumin, bilirubin, creatinine. We found significant improvement in platelets count, forty three percent of patients with platelet count below normal limit at baseline had values in normal range at end of treatment, which is in accordance with previous studies.…”
Section: Discussionmentioning
confidence: 70%